Design of a tailings pond relocated in front of a tailings contaminated in Ticapampa – Recuay – Ancash - Escalante Contreras, Jorge (2023)
The Ticapampa tailings deposit borders the left bank of the Santa River. The results of the geological, geomorphological, geodynamic and topographic investigations show a volume of 1,043,000.53 m3 of tailings, with a high content of acids, sulfates, dissolved mine metals, as well as copper and a large amount of suspended solids. Due to rainfall, the tailings are vulnerable to erosion, infiltration and contamination of the lower part. To mitigate contamination, a new impermeable tailings deposit was designed with a 1.5 mm thick HDPE geomembrane, which will be installed above geotextile with 400 gr/m2 nonwoven, where the tailings were encapsulated to monitor infiltration and movement. with a negative slope that produces acidic waters and contaminates the lower part. The geomembrane is made of high-density polyethylene (HDPE), its resins are high in molecular weight; This is how flexible geomembranes are formed, which are considered of good quality; It was formulated to resist the main chemical agents such as degradable ultraviolet rays.